The device for generating cold plasma in an electrically conductive solution, with the aim of tissue spare; Micro/Nanotechnologies and Electron Devices (EDM) - Zhumantaeva N. A. Nabat Abdesenovna; Lisitsyna L. A. Liliya Ivanovna; Maier V. I. Vladislav; Aleinik A. N. Aleksandr Nikonorovich; Pedder V. V. Valery Viktorovich (2016, 2016)
Title screen